2010
DOI: 10.1007/s00411-010-0267-3
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of 137Cs in a mouse model of chronic contamination by ingestion and effects on the hematopoietic system

Abstract: The aim of this work was to define the possible occurrence of hematological changes during the course of a chronic ingestion of (137)Cs. A mouse model was used, with ingestion through drinking water with a cesium concentration of 20 kBq l(-1). Ingestion started in parent animals before mating, and (137)Cs intake and its effect on the hematopoietic system was studied in offspring at various ages between birth and 20 weeks. (137)Cs content was measured in various organs, indicating that (137)Cs was distributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
22
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 41 publications
9
22
0
2
Order By: Relevance
“…Genetically predisposed Apolipoprotein E -/-(ApoE -/-) mice [36,37] were chronically exposed to 20, 100 or 500 Bq/animal of 137 Cs administrated through drinking water. Our dosing range (4-100 kBq/l) corresponded to a range spanning 5 times less and 5 times more than the concentration of 20 kBq/l used in previous studies [38]. More importantly, our ingestion rates are close to the estimated ingestion rates of 20 to 2100 Bq/day that were calculated to be ingested by humans living in contaminated areas [39].…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Genetically predisposed Apolipoprotein E -/-(ApoE -/-) mice [36,37] were chronically exposed to 20, 100 or 500 Bq/animal of 137 Cs administrated through drinking water. Our dosing range (4-100 kBq/l) corresponded to a range spanning 5 times less and 5 times more than the concentration of 20 kBq/l used in previous studies [38]. More importantly, our ingestion rates are close to the estimated ingestion rates of 20 to 2100 Bq/day that were calculated to be ingested by humans living in contaminated areas [39].…”
supporting
confidence: 69%
“…However, chronic ingestion of 20 kBq/l had no impact on leukocyte or lymphocyte numbers [38,53]. In our model,…”
Section: Discussionmentioning
confidence: 48%
“…However no pathological consequences were observed in association with these modifications (Lestaevel et al ., ). Moreover, no modifications of both immune and hematopoietic systems were found in a mouse model of 137 Cs chronic ingestion (Bertho et al ., , ).…”
Section: Introductionmentioning
confidence: 97%
“…We thus used our mouse model of chronic contamination through drinking water with a 90 Sr concentration of 20 kBq l −1 . Previous studies showed that this concentration led to a daily ingestion of 80–100 Bq per day and per animal (Bertho et al ., ; Synhaeve et al ., ), and give rise to whole body radiation dose of 10 mGy by the end of the 20 week study period (Bertho et al ., ). In this model, we study various parameters in order to delineate possible effects of 90 Sr chronic ingestion on two physiological systems, the hematopoiesis and bone physiology.…”
Section: Introductionmentioning
confidence: 99%
“…In mice chronically exposed to 137 Cs via ingested water, 137 Cs increased in muscles and kidneys with age until ca. 6 weeks without any gender differences (Bertho et al, 2010). This was explained as an effect of the continuous increase in ingestion of contaminated drinking water during the first 6 weeks of life.…”
mentioning
confidence: 98%